Anger and depressive ruminations as predictors of dysregulated behaviours in borderline personality disorder. (11th October 2017) - Martino, Francesca; Caselli, Gabriele; Di Tommaso, Jessica; Sassaroli, Sandra; Spada, Marcantonio M.; Valenti, Barbara; Berardi, Domenico; Sasdelli, Anna; Menchetti, Marco
Abstract: Background: Anger and depressive ruminations have recently received empirical attention as processes related to borderline personality disorder (BPD). The Emotional Cascade Model (Selby, Anestis, & Joiner, 2008) suggests that negative affect (such as anger and sadness) may trigger rumination, which in turn may increase the duration and extent of negative affect, leading to dysregulated behaviours aimed at reducing such intense and unpleasant emotions. Aim: The aim of this study is to explore the relationships between emotional dysregulation, anger and depressive ruminations, and their role in predicting dysregulated behaviours (such as aggression and self‐harm) in a clinical sample of patients with BPD. Methods: Ninety‐one patients with a diagnosis of BPD were recruited from three outpatient community mental health centres and asked to complete a comprehensive assessment for personality disorder symptoms, emotion dysregulation, anger and depressive ruminations, aggression, and self‐harm. Results: Anger and depressive ruminations were found to be significantly associated to, respectively, self‐harm and aggression, beyond the variance accounted by emotional dysregulation. Conclusions: Rumination may act as a mediator between emotional dysregulation and dysregulated behaviours in BPD. Future research should examine whether clinical techniques aimed at reducing rumination may be helpful in reducing dysregulated behaviours in patients with BPD.